2000
DOI: 10.1111/j.1365-2141.2000.02464.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ETV6/AML1 abnormalities in acute lymphoblastic leukaemia: incidence, alternative spliced forms and minimal residual disease value

Abstract: Summary. The t(12;21)(p13;q22) translocation, resulting in the fusion of the ETV6 and AML1 genes, occurs in 20±25% of paediatric B-lineage acute lymphoblastic leukaemias (ALL). The identification of the fusion product has important prognostic and therapeutic implications as the translocation has been associated with a favourable clinical outcome. The aim of this study was threefold: (i) to assess the frequency and clinical association of the fusion gene in patients with and without a cytogenetically detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A relatively high frequency of late relapses, i.e., off therapy, has been emphasized by several groups (Nakao et al , 1996; Harbott et al , 1997; Seeger et al , 1998, 1999; Takahashi et al , 1998; Avigad et al , 1999; Codrington et al , 2000; Tsang et al , 2001). In the present series, almost 50% of all relapses after 5 years and 80% of those after 6 years occurred in t(12;21)‐positive patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A relatively high frequency of late relapses, i.e., off therapy, has been emphasized by several groups (Nakao et al , 1996; Harbott et al , 1997; Seeger et al , 1998, 1999; Takahashi et al , 1998; Avigad et al , 1999; Codrington et al , 2000; Tsang et al , 2001). In the present series, almost 50% of all relapses after 5 years and 80% of those after 6 years occurred in t(12;21)‐positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the prognostic implications of t(12;21) have not reported individual data on gender and time in remission. However, the information that can be retrieved from studies providing pertinent data (Nakao et al , 1996; Harbott et al , 1997; Lanza et al , 1997; Satake et al , 1997; Loh et al , 1998; Rubnitz et al , 1999; Codrington et al , 2000; de Haas et al , 2000; Seeger et al , 2001; Tsang et al , 2001; Alvarez et al , 2005; Al‐Sweedan et al , 2007) does not support that boys generally relapse later than girls; based on all studies referred to above, the median remission duration before relapse was 37 months (range 17–102) for boys and 32 months (range 11–109) for girls. Thus, our finding may well be fortuitous and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation